Asian development review. - Asian Development Bank. (Manila, Philippines : Asian Development Bank, 1983)
online access available from 2008
Title from cover.
Keywords: Economische situatie; ECONOMIC DEVELOPMENT; ASIA; OCEANIA; Entwicklung; Entwicklungspolitik; Asien; Asiatisch-pazifischer Raum; Economic history; Asia -- Economic conditions -- Periodicals; Oceania -- Economic conditions -- Periodicals; Asia -- Economic conditions -- Periodicals; Oceania -- Economic conditions -- Periodicals; Asia; Oceania